A, The Dzikir Sebagai Upaya Menstabilkan Tingkat Emosional Orang Tua Menghadapi Kenakalan Remaja Prespektif Imam Al-Ghazali - Soeko Budi Waluyo, Tia Sal Syabila (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
This journal focuses on the problem of spiritual emptiness in today's society. The author explores how advances in science and rationalism may not only satisfy human desires for transcendental value, and how a balanced component of religion can help overcome this problem. This research specifically explores the science of Sufism, by focusing on the book Ihya' Ulumuddin by Imam Al-Ghazali. This writing takes a qualitative descriptive approach to analyze the concepts presented in the books by Imam Al-Ghazali. This allows for a deeper understanding of the topics to be covered. And in the formulation of the problem in this study, namely what dhikr is in accordance with the book of Imam Al-Ghazali and what are the effects of dhikr treatment applied by researchers on the emotionality of parents at Griya Kebon Agung 1 Sukodono Sidoarjo Housing Complex. The purpose of this study is that the problems that occur are: parents' emotional level anxiety, juvenile delinquency that occurs in children who are entering their teens, modern times are increasingly sophisticated, lack of understanding of the benefits of dhikr, and how parents control their emotions.